Preliminary studies on Acalypha indica: Proximate analysis and phytochemical screening - Mohd Nazri, Nurul Nadia; Hazali, Norazlanshah; Ibrahim, Muhammad A.; Masri, Mashita; Ayob, Mohdkhan (International Journal of Pharmacy and Pharmaceutical Science, 2016)
Objective: This study aims to evaluate the proximate composition and phytochemicals content of Acalypha indica. Methods: The dried samples of root, leaves, stem and whole plant were analysed for protein, total fat, ash, moisture, water activity and crude fibre according to guideline by Association of Official Analytical Chemist. The phytochemicals content were based on standard method. Results: The proximate analysis showed that the leaves contain the highest moisture (9.49%), ash (12.83%) and protein (23.98%). The root contains the highest carbohydrate (76.33%), crude fibre (42.05%) and gross energy (1453.94 kJ) content. The root also showed the lowest total fat (0.54+0.17%) and water activity (0.51+0.00 Aw). Besides that, the secondary metabolite such as alkaloid was identified in dried whole plant while tannin was detected in dried leaves and dried whole plant. The triterpenes, steroid and flavonoids were a presence in all samples analysed. Conclusion: The present of nutrition and phytochemicals support the traditional use of Acalypha indica as an alternative treatment for curing certain health conditions.